KECERDASAN EMOSIONAL GURU DAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Sulistia, Indryanti; Maryono, Maryono; Parandrengi, Resyarusyda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines teachers’ emotional intelligence and students’ learning motivation in Grade IV science and social studies (IPAS) learning at SDN 134/IV Kota Jambi. The study aims to: (1) describe the level of the teacher’s emotional intelligence in IPAS learning; (2) describe the level of students’ learning motivation; and (3) portray both variables simultaneously in the context of classroom learning. This research employed a quantitative descriptive design. The subjects consisted of one Grade IV teacher and 27 Grade IV students. Data were collected through observation and questionnaires, supported by interviews. The research instruments included observation sheets and questionnaires measuring teacher emotional intelligence and students’ learning motivation. Data were analyzed using descriptive statistical techniques, including score calculation, mean, and percentage, followed by categorization based on predetermined criteria. The findings indicate that the teacher’s emotional intelligence was categorized as very good, with an observation result of 90% and a questionnaire result of 92.5% (very high category). Students’ learning motivation was categorized as high, with a questionnaire percentage of 80.56%, supported by observation results showing most motivation indicators in the high to very high category. Descriptively, very good teacher emotional intelligence appeared alongside high student learning motivation in IPAS learning. It can be concluded that IPAS learning in Grade IV at SDN 134/IV Kota Jambi was conducted under supportive conditions in terms of teacher emotional intelligence and student learning motivation.